Tautomerism in 11-Hydroxyaklavinone: A DFT Study. (1st May 2012) - Türker, Lemi
Abstract : The antharquinone-based chromophore of 11-hydroxyaklavinone is present in the structure of an anticancer agent, daunomycin. On the other hand, aklavinone is the parent aglycone of certain anthracycline antibiotics that possess anti-cancer activity too. The structures of aklavinone and its 11-hydroxy derivative have many –OH groups, and two keto groups which may take place in certain tautomeric equilibria. Of these tautomeric forms, presently the one involving the anthraquinone based tautomers of 11-hydroxyaklavinone has been investigated quantum chemically in the framework of the density functional theory at the levels of RB3LYP/6-31G(d) and RB3LYP/6-31G(d, p).